Effect of ECH/ECCD on energetic-particle-driven MHD modes in helical plasmas. (1st June 2020) - Yamamoto, S.; Nagasaki, K.; Nagaoka, K.; Varela, J.; Cappa, Á.; Ascasíbar, E.; Castejón, F.; Fontdecaba, J.M.; García-Regaña, J.M.; González-Jerez, Á.; Ida, K.; Ishizawa, A.; et al.
Abstract: The effect of electron cyclotron heating (ECH) and electron cyclotron current drive (ECCD) on energetic-particle (EP)-driven magnetohydrodynamic (MHD) modes is studied in the helical devices LHD, TJ-II and Heliotron J. We demonstrate that EP-driven MHD modes, including Alfvén eigenmodes (AEs) and energetic particle modes (EPMs), can be controlled by ECH/ECCD. In the LHD device, which has a moderate rotational transform and a high magnetic shear, co-ECCD enhances toroidal AEs (TAEs) and global AEs (GAEs), while counter-ECCD stabilizes them, which improves the neutron rate compared with the co-ECCD case. Counter-ECCD decreases the core rotational transform and increases the magnetic shear, strengthening the continuum damping on the shear Alfvén continua (SAC). In the TJ-II device, which has a high rotational transform, moderate magnetic shear and low toroidal field period, helical AEs (HAEs) appear when the HAE frequency gap of the SAC is changed by counter-ECCD combined with a bootstrap current and neutral-beam-driven current. On the other hand, both co- and counter-ECCD are effective in stabilizing GAEs and EPMs in the Heliotron J device, which has a low rotational transform and low magnetic shear. The experimental results indicate that the magnetic shear has a stabilizing effect regardless of its sign. Modeling analysis using the FAR3d code shows that the growth rates are reduced by both co- and counter-ECCD in Heliotron J, reproducing the experimental results. ECH only affects EP-driven MHD modes, and the experimental results show that the effect depends on the magnetic configuration. In Heliotron J, some modes are stabilized with an increase in ECH power in the low-bumpiness magnetic configuration, while some modes are destabilized in the high- and medium-bumpiness magnetic configurations.